X-ray absorption and Raman spectroscopy studies of tungstates solid solutions ZncNi1-cWO4 (c=0.0-1.0) - Bakradze, Georgijs; Kalinko, Aleksandr; Kuzmin, Alexei (AIP Publishing, 2020)
The influence of thermal disorder and static distortions on the local structure in microcrystalline solid solutions of tungstates ZncNi1-cWO4 with c = 0.0–1.0 was investigated using temperature-dependent (10–300 K) x-ray absorption spectroscopy (XAS) at the W L3-edge. In addition, the vibrational properties of the solid solutions were studied by Raman spectroscopy. Our results indicate that the formation of solid solutions is accompanied by strong structural relaxations leading to the changes in the [WO6] octahedra distortions, which, in turn, affect the vibrational properties of tungstates. In particular, the frequency and band width of the highest W–O stretching mode at about 900 cm-1 show distinct composition dependence, following the local structure modifications as revealed by XAS.
G.B. acknowledges the ﬁnancial support provided by the State Education Development Agency for project No. 1.1.1.2/VIAA/3/19/444 (agreement No. 1.1.1.2/16/I/001) realized at the Institute of Solid State Physics, University of Latvia. A.K. and A.K. would like to thank the support of the Latvian Council of Science project No. lzp-2019/1-0071. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; ZnWO4; NiWO4; tungstates; solid solutions; X-ray ab- sorption spectroscopy; Raman spectroscopy